2007
DOI: 10.1111/j.1552-6569.2007.00097.x
|View full text |Cite
|
Sign up to set email alerts
|

Neuroimaging and Neurologic Complications after Organ Transplantation

Abstract: Neurologic complications are common after transplantation and affect 30-60% of transplant recipients. The etiology of most of the posttransplant neurologic disorders is related to the opportunistic infections, both systemic and involving central nervous system (CNS), toxicity of immunosuppressive medications, and the metabolic insult created by the underlying primary disease and the transplant procedure. Neuroimaging studies are one of the key tools in the evaluation and enable early diagnosis of neurologic co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(16 citation statements)
references
References 96 publications
(186 reference statements)
0
15
0
1
Order By: Relevance
“…It usually presents late in the posttransplant period, with a median onset of 27 months after transplantation manifesting with slowly progressive cognitive impairment, visual symptoms and ataxia in a large series [39]. The classic pattern on neuroimaging shows multiple subcortical white matter lesions without contrast enhancement [38]. Unfortunately, there is no effective antiviral therapy for PML, and the only treatment strategy is to reduce immunosuppression [39].…”
Section: Opportunistic Infectionsmentioning
confidence: 98%
See 1 more Smart Citation
“…It usually presents late in the posttransplant period, with a median onset of 27 months after transplantation manifesting with slowly progressive cognitive impairment, visual symptoms and ataxia in a large series [39]. The classic pattern on neuroimaging shows multiple subcortical white matter lesions without contrast enhancement [38]. Unfortunately, there is no effective antiviral therapy for PML, and the only treatment strategy is to reduce immunosuppression [39].…”
Section: Opportunistic Infectionsmentioning
confidence: 98%
“…Human herpes virus 6 (HHV-6) is increasingly being recognized as a cause of limbic encephalitis in SOT recipients which may manifest with encephalopathy, amnesia, and/or seizures [36,37]. Neuroimaging studies often demonstrate characteristic bilateral involvement of the mesial temporal lobes; however, imaging studies may be normal and cannot substitute for cerebrospinal fluid testing [36,38].…”
Section: Opportunistic Infectionsmentioning
confidence: 98%
“…2a); however, this may not be the case in acute or subacute cases. Because aspergillosis is a vasoinvasive pathogen, evidence of hemorrhagic brain infarction may also be seen on neuroimaging studies [112]. One group of investigators have suggested that ''target-like'' lesions on DWI may aid in distinguishing Aspergillus from other fungal causes of brain abscess and malignancy [113].…”
Section: Aspergillus Speciesmentioning
confidence: 98%
“…4,5 Neurologic complications can be related to surgical procedures, immunosuppression after transplant (including opportunistic infections or neurotoxicity of drugs), metabolic disturbances, malignancies, and stroke. [6][7][8] A common neurologic complication of kidney transplant at our hospital was femoral neuropathy (Table 1), similar to previous reports.…”
Section: Discussionmentioning
confidence: 99%